Equibrilliant Gameboard Assessment to Increase Students’ Conceptual on Chemical Equilibrium - Rusli, Nurul Hanani; Ali, Sariah; Abdul Talib, Corrienna; Hanri, Chuzairy; Rosli, Nur Adilah; Shobri, Nurul Nazatul Shahizah Mahamad; Ong, Eng Tek (Universitas Muhammadiyah Purwokerto, 2023)
Equibrilliant is a game-board assessment to improve students' conceptual understanding of Chemical equilibrium. This game-based learning teaching material aims to overcome pro-long misunderstandings by teacher's quick feedback and enhance students' motivation through the enjoyment of play-learning. This approach applies the formative assessment to replace conventional assessment which limits the evaluation of students’ progress, contributes to prolonged misconceptions, and creates a stressful situation and low motivation. Analysis of findings through pre-posttest reveals that Equibrilliant gameboard assessment has improved 50% of students’ conceptual achievement and provides high impact assessment with a high mean score of 4.64. Utilizing Equibrilliant is a better way of assessing students’ concepts to prepare matriculation graduates as knowledgeable, innovative, and competitive in the STEM field in the future.